PELATIHAN PENGGUNAAN PLATFORM MICROSOFT SEBAGAI MEDIA PEMBELAJARAN DARING - Gohzali, Hernawati; Lubis, Ali Akbar (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
The unconducive pandemic situation has greatly affected various aspects of human life, including education. Learning that used to be done face-to-face must change to online learning. Online learning is distance learning based on internet network technology such as video conference, video call or text chat. The ability to use devices that can support the online learning process is needed by students in order to have a better learning experience. An application that can facilitate students in collaborating, communicating, and sharing learning documents is Microsoft Teams. Based on the results of the perception test conducted, it was found that the participants were familiar with several software that support online learning process. But for Microsoft platform itself, they are not familiar with and understand its use. To overcome the students' problems, a service activity was carried out to provide training on the use of Microsoft Teams application. Training activities were carried out twice and the evaluation process was carried out by giving assignments and working on pre-test and post-test questions. Various features from Microsoft are used by the students for online learning, including conversation features, meeting, cloud storage (onedrive), collaboration on the same worksheet in Microsoft Office, and so on. From the results of working on pre-test and post-test questions, it shows that there is an increase in students' skills in using the Microsoft Teams application.